STUDY OF EFFECTS FEEDING ALBIZIA LEBBECK LEAF ON SOME BLOOD BIOCHEMICAL PARAMETERS ON ONE-HUMPED CAMEL - Khadijeh Ansari; Tahereh Mohammad abadi; Mohsen Sari (Basrah Journal of Veterinary Research)
Albizia lebbeckor sirisis a tropical legume and is the most widespread of Albizia genus inthe world. The leaveof Albizia lebbeckhas a low content of tannins and phenoliccompoundsand relatively high content of N and Ca. The aim of this experiment was toinvestigate of feeding of Albizia lebbeck as a replacement for alfalfaon blood parametersofone-humped camel. Four dromedary camels (2 fistulated) about 2 years old and 150-200 kgweight of the Arabi breed were selected. They were fed for about one month with control diet(60% bagasse+40% alfalfa) or diet without Albizia lebbeckand diet containing Albizialebbeck(100 percent of alfalfa) by two periods. In the end of trial, blood samples wereobtained and some metabolites were measured. The results showed that the replacing Albizialebbeck with alfalfa in one-humped camel had not any effect on blood factors. Glucose levelsin control and experimental diet was 112 and 108.25 mg/dl, respectively. Feeding Albizialebbeck during the experimental period, had no significant effect on blood urea nitrogen andtriglyceride. Cholesterol content of control and experimental diets was 25.75 and 26 mg/dl,respectively. According to the results of this study, replacing Albizia lebbeckleaf for alfalfa indiet of one-humped camel did not change blood urea nitrogen, glucose, cholesterol andtriglyceride, therefore it may be used by 100 % alfalfa in one-humped camel diet.